Anaesthesia, Pain, and Intensive Care Medicine Training in Malta - Attard Cortis, Petramay (Journal of the Portuguese Society of Anesthesiology, 2024)
A description on the organization of the Anaesthesia, Pain, and Intensive Care Medicine Training in Malta is provided.